Tip speed ratio control of a 200 kW VAWT with synchronous generator and variable DC voltage. Issue 3 (5th November 2013) - Eriksson, Sandra; Kjellin, Jon; Bernhoff, Hans
Abstract A novel control method for a fixed‐pitch variable speed wind turbine is introduced and experimental results are presented. The measured absorbed power and rotational speed, together with a look‐up table for the aerodynamic efficiency, are used to estimate the wind speed reaching the turbine as well as the tip speed ratio. Thereby, the control is independent on wind speed measurements and the wind turbine itself is used as an anemometer. Tip speed ratio control is implemented by comparing the estimated tip speed ratio to a reference value and adjusting the DC voltage level accordingly. Tip speed ratio control benefits from that the aerodynamic efficiency hardly varies with changing tip speed ratio when close to its optimum value. Experimental results from a 200 kW vertical axis wind turbine are presented. The voltage from the permanent magnet generator is passively rectified and the alternating DC voltage is then inverted, filtered, transformed, and grid connected. The estimated wind speed is compared with the measured wind speed. The absorbed power when tip speed ratio control has been implemented is shown. It is concluded that the presented control method works and some future improvements are discussed.